LA Enseñanza-aprendizaje en ciencias sociales a través de ilustraciones artísticas: un estudio de caso - Coronado Martín, Jesús Angel (Revista Ecos de la Academia, 2022)
The illustrations give way to the imagination by representing information visually, being a teaching-learning strategy suggested in the constructivist pedagogical model because it allows significant learning. The objective of this work was to improve teaching-learning in social sciences based on illustrations through their application and evaluation to eighth-year students in the Unidad Educativa "San Francisco" (Ibarra). The research has a mixed approach; quantitative in relation to data from the evaluations and qualitative when having the opinions of the students during the classes. The results were obtained from the comparison between a traditional class and one in which artistic illustration was applied. In the traditional class, boredom and forced participation were evidenced, while in the class with illustrations, the participants showed more motivation and participation with respect to the subject, so implementing the illustrations improves teaching-learning in social sciences and due to this experience, it could work in other areas.